O desenvolvimento do pensamento teórico de estudantes do quinto ano na aprendizagem dos números racionais e do conceito de medida - Pereira, Helaina de Fátima Vinhas (2021)
The present research aimed to analyze the development of theoretical thinking in signification processes generated by fifth grade elementary school students in a triggering-situation of learning of rational numbers and the concept of measure, titled The journey and the mysterious friend . Based on the assumptions of historical-dialectical materialism (Karl Marx, Pável Kopnin) and the cultural-historical theory (Lev S. Vigotski, Alexei Leontiev, Vasily Davidov), it was presented this exploratory research, outlined as a case study, in a qualitative approach, in a public school in the interior of Minas Gerais, to answer the following question: what senses and meanings do students make explicit, in their activity, in a triggering-situation of learning of rational numbers and the concept of measurement? The specific objectives were to analyze whether the triggering-situation of learning elicited student activity and to identify the senses and meanings produced. The data analysis based on the constitution of the meaning cores, which make explicit the conceptual connections of the rational number and the measure, as well as the evidence of the development of students' autonomy. The research provided a closer relationship between academic knowledge and school praxis, furthermore the re-signification of teaching practice and the intellectual autonomy of students, through the development of mathematical argumentation and reasoning. In addition to this report, an educational product was developed: a didactic unit, attached to this research.